Changes in University Teacher’s Pedagogical Activity in the Context of Digitalization of Education - I. S. Batrakova; E. N. Glubokova; S. A. Pisareva; A. P. Tryapitsyna (Высшее образование в России)
The purpose of this article is to consider the changes in university teacher’s pedagogical activity in the conditions of a rapid transformation of higher education and propose a theoretical and empirical substantiation of the importance of teacher’s understanding of the value-semantic attitude to pedagogical activity, which is not limited only to mastering digital competencies, but consists in mastering pedagogical knowledge that allows you to critically analyze the productivity of modern educational strategies and methods.The conducted research was based on the methodology of post-non-classical science, which implies the widespread use of qualitative research methods that reflect the convergence of explanatory and interpretative research approaches, the use of representations, opinions, attitudes, and values of the research participants as full data.The article describes the results of studying the university teachers’ attitude to changes, the value orientations of the ongoing changes, as well as the main difficulties faced by university teachers in the context of digitalization of education – the design of educational and training programs, modern educational and methodological complex, the organization of productive self-directed work and communication with students in the educational process.The main directions of overcoming the identified difficulties are given – the construction of flexible curricula within the framework of the Federal State Educational Standard of Higher Education, the development of the digital educational environment of the university and updating the content of the professional development programs for teaching staff. The conclusion is made about the increasing importance of pedagogical knowledge in teacher’s professional activity in the conditions of a modern university.